TRAPS mutations in Tnfrsf1a decrease the responsiveness to TNFα via reduced cell surface expression of TNFR1 - Akagi, Takahiko; Hiramatsu-Asano, Sumie; Ikeda, Kenta; Hirano, Hiroyasu; Tsuji, Shoko; Yahagi, Ayano; Iseki, Masanori; Matsuyama, Makoto; Mak, Tak W.; Nakano, Kazuhisa; Ishihara, Katsuhiko; Morita, Yoshitaka; et al. (Frontiers in Immunology, 2022)
Tumor necrosis factor (TNF) receptor-associated periodic syndrome (TRAPS) is an autoinflammatory periodic fever syndrome associated with heterozygous mutations of TNFRSF1A which encodes TNF receptor type I (TNFR1). Although possible pro-inflammatory mechanisms have been proposed, most previous studies were performed using in vitro overexpression models, which could lead to undesirable inflammatory responses due to artificial overexpression. It is crucial to reproduce heterozygous mutations at physiological expression levels; however, such studies remain limited. In this study, we generated TRAPS mutant mice and analyzed their phenotypes. Three Tnfrsf1a mutant strains were generated by introducing T79M, G87V, or T90I mutations. T79M is a known mutation responsible for TRAPS, whereas G87V is a TRAPS mutation that we have reported, and T90I is a variant of unknown significance. Using these murine models, we investigated whether TRAPS mutations could affect the inflammatory responses in vivo and in vitro. We found that all mutant mice exhibited no detectable inflammatory phenotypes under standard housing conditions for one year. Interestingly, TRAPS mutant (T79M and G87V) mice had reduced mortality rates after the administration of lipopolysaccharide (LPS) and D-galactosamine, which induce TNFα-dependent lethal hepatitis. Moreover, TRAPS mutations strongly suppressed the development of TNFα-mediated arthritis when crossed with human TNFα transgenic mice. In in vitro primary bone marrow-derived macrophage cultures, the T79M and G87V mutations attenuated the inflammatory responses to TNFα compared to the wild-type, while these mutations did not alter the responsiveness of these cells to LPS. The T90I mutant macrophages behaved similarly to wild type in response to LPS and TNFα. The TNFR1 protein was increased in whole-cell lysates of TRAPS mutant macrophages, whereas the cell surface expression of TNFR1 was significantly decreased in TRAPS mutant macrophages. Taken together, TRAPS mutations did not augment the inflammatory responses to TNFα and LPS; instead, they suppressed the response to TNFα via decreased cell surface expression of TNFR1. The stimulation of lymphotoxin-α, adenosine triphosphate (ATP), and norepinephrine in primary macrophages or various stimuli in murine splenocytes did not induce detectable inflammatory responses. In conclusion, TRAPS mutations suppressed responsiveness to TNFα, and TRAPS-associated inflammation is likely induced by unconfirmed disease-specific pro-inflammatory factors.